2018
DOI: 10.1186/s13756-018-0361-x
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequencing reveals high clonal diversity of Escherichia coli isolated from patients in a tertiary care hospital in Moshi, Tanzania

Abstract: BackgroundLimited information regarding the clonality of circulating E. coli strains in tertiary care hospitals in low and middle-income countries is available. The purpose of this study was to determine the serotypes, antimicrobial resistance and virulence genes. Further, we carried out a phylogenetic tree reconstruction to determine relatedness of E. coli isolated from patients in a tertiary care hospital in Tanzania.MethodsE. coli isolates from inpatients admitted at Kilimanjaro Christian Medical Centre bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 48 publications
10
21
1
Order By: Relevance
“…Relatively little data concerning the genomics of E. coli exist in Africa to date. [21][22][23][24] The isolates sequenced as part of our project collected in Lilongwe, in the central region of Malawi, are highly phylogenetically similar to those seen in a previous study conducted in Blantyre, Malawi, in the southern region. [27] Interestingly, there are multiple branches that contain nearly identical isolates sequenced between the two studies despite the fact that the collection sites are over 300km apart from each other and our isolates were on average collected several years later.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Relatively little data concerning the genomics of E. coli exist in Africa to date. [21][22][23][24] The isolates sequenced as part of our project collected in Lilongwe, in the central region of Malawi, are highly phylogenetically similar to those seen in a previous study conducted in Blantyre, Malawi, in the southern region. [27] Interestingly, there are multiple branches that contain nearly identical isolates sequenced between the two studies despite the fact that the collection sites are over 300km apart from each other and our isolates were on average collected several years later.…”
Section: Discussionsupporting
confidence: 70%
“…[27] Although globally there is a strong association between ST131 and presence of the bla CTX-M-15 gene, here we identify the bla CTX-M-15 gene across a diverse set of lineages. [11] This finding is similar to other studies in Tanzania and Malawi, where the bla CTX-M-15 gene was found across numerous ST. [22,27] We see the bla gene in 8 different sequence types, including ST131. The ST that most commonly contained the bla CTX-M-15 gene was ST410.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There also has been no clear time-dependent shifting of these lineages, though it appears that ST167 and ST617 are the dominant O89b-containing strains. ST617 strains are also known to carry many antibiotic resistance genes (3033).…”
Section: Resultsmentioning
confidence: 99%
“…GZ04-0086 belonged to phylogenetic group A and sequence type ST44. E. coli ST44 has been frequently isolated from clinical settings (Kanamori et al, 2017;Runcharoen et al, 2017;Sonda et al, 2018). A phylogenetic analysis of E. coli ST44 revealed that GZ04-0086 was closest to isolates DO40 from canine and RDK06_431D from a patient in Tanzania, with 51 and 54 SNPs, respectively (Supplementary Figure S2).…”
Section: Genomic Insights Through Short-read and Long-read Sequencingmentioning
confidence: 99%